Agenda Komunikasi Publik yang Dilupakan dalam Pemilu - RISANG RIMBATMAJA (Universitas Muhammadiyah Yogyakarta, 2013)
So far public communication is running tend to individually. It is very important to revised it. To vote on general election is individual right, but political participation is not always on individual action. Organized of public group have to develop as the alternative way to opposite of power abuse from political elite. Political elite frequently exploitation the voters with the false promises and corruption after they to be political actors. Public communication must support of critical discussion between society group and in society. Here we assume that every people in their community, they have potential to develop their agenda and create dialogue by their self. The assumed that dialogue in their communities tend to freefrom anti pluralism because the topic on discussion in their communitiesbased on their interests. So it is very possible, the issues of anti pluralismdidn’t emerge in their communities discussion, but tend to access of education, health and public services issues. Keywords : communication agenda, public, election